2005
DOI: 10.1103/physrevb.72.235410
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of the absence of spin diffusion in multipulse NMR experiments on diluted dipolar solids

Abstract: Puzzling anomalies previously observed in multipulse NMR experiments in natural abundance 29 Si [A.E. Dementyev, D. Li, K. MacLean, and S.E. Barrett, Phys. Rev. B 68, 153302 (2003)] such as long-lived spin echoes and even-odd asymmetries, are also found in polycrystalline C60. Further experiments controlling the phases and tilting angles of the pulse trains, as well as analytical and numerical calculations allowed us to explain the origin of these anomalies. We prove that the observation of long magnetization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 20 publications
2
40
1
Order By: Relevance
“…Similar situations were observed in all the systems that manifest long decay times when CPMG-like sequences are applied [12,43,44].…”
Section: Controlled Generation Of Pseudocoherencesmentioning
confidence: 51%
See 4 more Smart Citations
“…Similar situations were observed in all the systems that manifest long decay times when CPMG-like sequences are applied [12,43,44].…”
Section: Controlled Generation Of Pseudocoherencesmentioning
confidence: 51%
“…It can be observed that the stimulated echoes appear 1 ms after the last pulse (remember that they should not be formed with perfect p pulses) and they show a phase that coincides with or is opposite to that of the Hahn echo, which appears at t 1 − t = 14 ms, for the CPMG1 STE and CPMG2 STE , respectively. A phenomenological explanation for the long magnetization tails based on the constructive or destructive interference between the stimulated and normal echoes was reported by us in a previous paper [43] and later on verified through hole burning experiments [44]. Thus, although disappointing for the experimentalists of the quantum information community, we concluded that the observed long tails in the magnetization decays are a signature not of long decoherence times but of the recovery of coherences saved as polarization.…”
Section: Long-lived Signalsmentioning
confidence: 69%
See 3 more Smart Citations